Dependence of Water Vapour Adsorption on the Polarity of the Graphene Surfaces of Multi-Wall Carbon Nanotubes - Robert H. Bradley; Aurik Andreu; Kelby Cassity; Susan Osbeck; Rodney Andrews; Mark Meier; Colin Johnston (Adsorption Science & Technology)
The adsorption of water by the graphene surfaces of multi-wall carbon nanotubes (MWCNTs) in either the untreated (4.3 atom% oxygen) or oxidised (22.3 atom% oxygen) surface states has been studied. Different concentrations of surface oxygen groups, which have been directly measured using XPS, give rise to distinctly different shapes of water adsorption isotherms. Those from the untreated materials follow the pressure axis which lends them a Type III character in the BDDT classification. However, since they display a clear point of inflection at the lowest pressure, they are strictly speaking Type II isotherms but indicative of relatively few polar interactions and weak water adsorptivity. In sharp contrast, the isotherms from the oxidised MWCNTs are typically Type II and are characterised by a marked positive curvature in their low pressure region due to the increased numbers of specific interactions occurring between water molecules and the polar surface oxygen groups. The water adsorption data were modelled by the equation of D'Arcy and Watt with a direct correlation being observed between the surface polarity parameters (a mL and a 0 ) and also a s (the limiting water uptake) and the surface oxygen levels of the MWCNTs. The difference in polar surface energy was confirmed by measurements of the calorimetric enthalpies of immersion in water (Δh i ), which were −54 mJ/m 2 for the untreated and −192 mJ/m 2 for the oxidised materials. These values also reflect the difference in the integral net enthalpies of adsorption for the two hydrophilic surfaces: a value of ca. −35 mJ/m 2 being obtained for an oxygen-free (hydrophobic) surface. Water adsorption on these hydrophilic graphene surfaces was shown to occur by specific hydrogen bonding and was therefore strongly dependent on the numbers of oxygen-containing polar surface sites. This behaviour is well known for other types of porous and non-porous carbon materials and is also predicted for carbon nanotubes by molecular simulation studies. The work described herein therefore provides early experimental confirmation of the quantitative role of surface oxygen chemistry in determining the water adsorption character of MWCNT graphene surfaces; it also validates previous simulation studies.